ANALISA GUGUS FUNGSI PADA NANOPARTIKEL MAGNESIUM FERRITE (MgFe2O4) YANG DIENKAPSULASI DENGAN POLYETHYLENE GLYCOL (PEG-4000) DAN SILIKA - Deska Lismawenning Puspitarum (Journal of Science and Applicative Technology, 2018)
Magnesium Ferrite Magnesium (MgFe2O4) magnetic nanoparticles have been successfully carried out by varying the concentrations of PEG-4000 and silica as encapsulation materials using coprecipitation methods. The X-ray Diffraction (XRD) analysis showed that new phases appeared in MgFe2O4 after PEG-4000 encapsulation, ie Î±-Fe2O3 having a paramagnetic rhombohedral and Î³-FeO (OH) structure. The particle size of MgFe2O4 before encapsulation was 10.5 nm, after encapsulation with PEG-4000 became 5.2 nm and encapsulation with silica became 18.8 nm. In encapsulation with silica, the peak of the new diffraction field 222 which is a crystal appears. The result of Fourier Transform Infra-Red (FTIR) analysis showed that in MgFe2O4 coated with PEG-4000, there was a shifting in the wave number 2885.5 cm-1 to 2924.1 cm-1 in CH bond which was the bond of PEG- 4000 and a shifting in the wave number 316.3 cm-1 to 300.9 cm-1 on the metal oxide bond (MO) which is a uniform pattern of MgFe2O4. The presence of silica which has coated the magnetic material is shown in the 455.2 cm-1 number of Si-O-Si (bending) group.